Post-orogenic, Carboniferous granite hosted Sn-W mineralization in the Sierras Pampeanas Orogen, North-western Argentina. - Fogliata, Ana Silvia (2012)
The Sierras Pampeanas orogen, in northwestern Argentina, hosts significant Sn-W mineralization in a variety of mostly epizonal granite stocks emplaced in variably metamorphosed country rocks. The San Blas, Huaco and El Durazno granite stocks in the Sierra de Velasco, the La Quebrada granite in the Sierra de Mazán, the Cerro Colorado granite in the Cerro Negro, and the Los Mudaderos and Sauce Guacho granite stocks in the Sierra de Ancasti, are largely peraluminous (ASI between 1.05 and 1.38) and represent S-type granites, are strongly fractionated (i.e., high Rb/Sr ratio), have a low oxidation state (low Fe2O3/FeO ratio) and are geotectonically linked to syncollisional magmatism. The U-Pb SHRIMP analyses on zircons from the Cerro Colorado and La Quebrada granites, located in the Cerro Negro and Sierra de Mazán, respectively, revealed ages from Lower Ordovician (Tremadocian) to Carboniferous. All granites display elevated LREE values, low HREE values and negative Eu anomalies. With regards to total REE values, two groups of granite stocks can be recognized. The granites with lower REE contents are highly evolved granites and are related to Sn-W mineralization. The mineralized granites display higher values of Sn, W and Rb, and lower values of Sr and Ba compared to barren granites. These trace element characteristics appear to be diagnostic for Sn-W mineralized granite stocks in the western Sierras Pampeanas. The western Sierras Pampeanas contains locally geochemically evolved Carboniferous granites, which are interpreted to be the main control of significant Sn-W mineralization. The Carboniferous age of western Sierras Pampeanas Sn-W mineralization sets it apart from the Triassic age of the Sn?W mineralization in the Eastern Tin belt of Bolivia.